Long-term administration of IMT504 greatly improves the diabetic condition in female NOD mice: impact on the immune system - Lavignolle Heguy, María del Rosario (2019)
Due to the importance of type I Diabetes, it has become crucial to find a treatment that would not only normalize blood glucose, but also restore insulin secretion by stopping the autoimmune destruction of beta cells. Our approach for the reversion of the diabetic condition consists of the use of an immunomodulatory oligonucleotide, IMT504 (IMT). Previously, we have shown that IMT treatment promotes a marked recovery of toxic diabetes in rats, immunodependent diabetes in mice and in a short-term treatment in diabetic NOD mice. Here we evaluate a continuous and chronic IMT treatment in NOD diabetic mice, more similar to what could eventually be used in humans. We have previously shown that this treatment improves the metabolic condition and we aim here to study its immunological effects. Diabetic female NOD mice were implanted with constant drug release pumps, loaded with either IMT (total dose released per day: 20 mg/kg BW) or saline. After 28 days of treatment, mice were sacrificed, and their spleens and pancreases harvested for gene expression analysis by RT-qPCR and leukocyte infiltration determination (haematoxylin and eosin staining) respectively. Ongoing results show that IMT induces a decrease in leukocyte infiltration in Langerhans islets (p<0.05). Regarding gene expression in splenocytes, we observed in the treated group, an up-regulation of Indoleamine 2,3-deoxygenase 1 (p<0.0001) and Galectin-3 genes (p<0.05), down regulation of Interleukin-4 (p<0.001) and Interferon-γ (p<0.05), but no differences in Transforming growth factor-β expression compare to controls. We conclude that a continuous and prolonged IMT treatment alters the immune response of diabetic mice, by changes in the expression of genes coding for pro and anti-inflammatory proteins involved in the immune pathways of the disease, and thereby results in a decrease in the immunological infiltration of pancreatic islets.